Artificial Intelligence and Ethics Accounting: Transparency and Trust Issues in Financial Audits - Amini, Rostam (International Journal of Business Management and Entrepreneurship, 2025)
The integration of Artificial Intelligence (AI) into the field of auditing has the potential to significantly enhance audit performance, improve the accuracy of financial reporting, and foster innovation within service-based organizations. These technologies help create an intelligent and ethically-aware audit environment that contributes to improving both the quality and reliability of audit outcomes. However, the adoption of AI in auditing also introduces a range of ethical and practical challenges. Key concerns include maintaining ethical integrity within algorithms, ensuring data privacy, managing human-machine interactions, addressing power imbalances and accountability, and promoting ethical flexibility. Despite these challenges, AI offers substantial opportunities to advance the profession. These include reconciling performance with ethical standards, increasing transparency, managing risks more effectively, embedding ethical principles into algorithms, enhancing accuracy and efficiency, improving predictive capabilities, establishing new ethical frameworks, and developing human skills in alignment with AI systems. Ultimately, the successful application of AI in auditing depends on preserving ethical values, addressing emerging challenges proactively, and employing these technologies wisely. This underscores the ongoing need for ethical vigilance and responsiveness to social and moral implications. The remainder of this paper provides a detailed examination of current research related to ethics, artificial intelligence, and the auditing profession.